The Phosphatidylinositol 3‐kinase Class III Complex Containing TcVps15 and TcVps34 Participates in Autophagy in Trypanosoma cruzi. (23rd September 2016) - Schoijet, Alejandra C.; Sternlieb, Tamara; Alonso, Guillermo D.
Abstract: Autophagy is a degradative process by which eukaryotic cells digest their own components to provide aminoacids that may function as energy source under nutritional stress conditions. There is experimental evidence for autophagy in parasitic protists belonging to the family Trypanosomatidae. However, few proteins implicated in this process have been characterized so far in these parasites. Moreover, it has been shown that autophagy is involved in Trypanosoma cruzi differentiation and thus might have a role in pathogenicity. Here, we report the cloning and biochemical characterization of TcVps15. In addition, we demonstrate that TcVps15 interact with the PI3K TcVps34 and that both proteins associate with cellular membranes. Under nutritional stress conditions, TcVps15 and TcVps34 modify their subcellular distribution showing a partial co‐localization in autophagosomes with TcAtg8.1 and using an active site TcVps15‐mutated version (TcVps15‐K219D‐HA) we demonstrated that this relocalization depends on the TcVps15 catalytic activity. Overexpression of TcVps15‐HA and TcVps15‐K219D‐HA also leads to increased accumulation of monodansylcadaverine (MDC) in autophagic vacuoles under nutritional stress conditions compared to wild‐type cells. In addition, the MDC‐specific activity shows to be significantly higher in TcVps15‐HA overexpressing cells when compared with TcVps15‐K219D‐HA. Our results reveal for the first time a role of TcVps15 as a key regulator of TcVps34 enzymatic activity and implicate the TcVps15‐Vps34 complex in autophagy in T. cruzi, exposing a new key pathway to explore novel chemotherapeutic targets.